Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations